Long-term results of tibialis posterior tendon transfer for drop-foot - Yeap, J.S.; Birch, R.; Singh, D. (Springer, 2001)
Twelve patients with drop-foot secondary to sciatic or common peroneal nerve palsy treated with transfer of the tibialis posterior tendon were followed-up for a mean of 90 (24-300) months. In 10 patients the results were 'excellent' or 'good'. In 11 patients grade 4 or 5 power of dorsiflexion was achieved, although the torque, as measured with a Cybex II dynamometer, and generated by the transferred tendon, was only about 30% of the normal side. Seven patients were able to dorsiflex their foot to the neutral position and beyond. The results appeared to be better in men under 30 years of age with common peroneal palsies. A painful flatfoot acquired in adulthood does not appear to be a significant long-term complication despite the loss of a functioning tibialis posterior tendon.